Could negotiation among agents be regarded as an argumentative process? - Stankevicius, Alejandro G. (2000)
The building of an intelligent agent has become the main concern of Artificial intelligence (Al). Unfortunately, this enterprise proved to be unattainable, in particular given the complexity involved with the formal definition of intelligence. To overcome this problem, several researchers suggested the notion of rational agents as a substitute for the notion of intelligent agent. Consequently, mainstream Al nowadays strives for defining what a rational agent is.